Manejo da adubação com sulfato de amônio no desempenho produtivo do milho cultivado após aveia e trigo - Goncalves Silva, Maria Anita (2014)
The time, dose and applied nutrients in corn have a direct effect on its productivity. Therefore, the objective was to study the application of N and S in corn as ammonium sulfate, in succession to wheat and oats and evaluate different forms of fertilizer management. The experiment was conducted in a randomized block design in Oxisol (Hapludox). The five treatments with N, at a dose of 120 kg ha(-1) were applied in 20 plots (5x4), according to the management of fertilizer: T1-N (120 kg ha(-1)) full at sowing, T2-N (120 kg ha(-1)) total coverage; T3-N (40 kg ha(-1)) at sowing and N (80 kg ha(-1)) in coverage; T4-N advance in wheat sowing and sowing oats (120 kg ha(-1)), T5-(control). The S doses were corresponding to their concentrations in the fertilizer. Only wheat received a dose of 24 kg N ha(-1) at sowing all plots and oats received 24 kg N ha(-1) at sowing only the portions related to treatment with anticipation of corn N (T4). We evaluated the biomass production of winter crops (oats and wheat), according to the fertilization at sowing, and also the influence of winter crops and management of ammonium sulfate, the corn yield. The oats produced more dry matter in relation to wheat, positively influencing the corn yield, regardless of fertilizer management. The anticipation of ammonium sulfate, the sowing of oats, was favorable to corn yield, equating to other forms of management of fertilizer. Rotation corn and oats, forms management, ammonium sulphate, at seeding, topdressing or applied in split were equally efficient in corn yields.